Instructional Supervision and Clan Culture as Correlates of Teachers’ Service Delivery in Public Secondary Schools in Anambra State - Okaforcha, Choice Chimaa; Otugo, Samuel Ogechukwu (Education and Development Research, 2026)
The quality of teachers’ service delivery in public secondary schools in Anambra State has been a persistent concern, often linked to low student performance, inadequate instructional supervision, and weak organizational culture. The study used a correlational research design to examine how school administrative practices and organizational culture relate to teachers’ service delivery in Anambra State public secondary schools. The population consisted of 6,598 teachers across six education zones, with a sample of 660 selected through multistage and proportionate random sampling. Data were collected using three structured questionnaires on administrative practices, organizational culture, and teachers’ service delivery, validated by experts and tested for reliability with Cronbach Alpha coefficients above 0.70. Questionnaires were administered directly, yielding 618 valid responses. Data were analyzed with Pearson correlation using SPSS to determine the strength and direction of relationships among the variables. The study examined the correlation between instructional supervision, clan culture, and teachers’ service delivery in public secondary schools in Anambra State with a sample of 618 teachers. Results showed a strong positive correlation between instructional supervision and teachers’ service delivery (r = 0.806, p = 0.000), indicating that better supervision significantly enhances service delivery. Similarly, clan culture exhibited a very strong positive correlation with teachers’ service delivery (r = 0.846, p = 0.000), suggesting that supportive cultural values within schools positively influence teacher effectiveness. Both null hypotheses were rejected, confirming significant relationships between the variables. The study concludes that consistent instructional supervision and a supportive clan-based organizational culture are critical for enhancing teachers’ service delivery in public secondary schools.